PENGARUH CITRA MERK DAN BAURAN PEMASARAN TERHADAP KEPUTUSAN MEMILIH LEMBAGA PELATIHAN KERJA SWASTA - Ni Kadek Swandayani; Trianasari -; Ni Luh Wayan Sayang Telagawathi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this research is to examine the interaction between the following factors: (1) brand image; (2) products; (3) price; (4) promotion; (5) place; (6 people; (7) process; (8) physical evidence; and (9) brand image, product, price, promotion, place, physical evidence, process, people, and togetherness. Quantitative clause approach is used for this research. Purposive sampling was used to select 66 students from class X training at LPK Royal Bali College during the second semester for this study. This study used a questionnaire to collect data, which was then analyzed by means of a regression test. The research results show that: (1) brand image has a significant impact on choosing decisions, (2) product has a significant impact on choosing decisions, (3) price does not have a significant impact on choosing decisions, (4) promotion does not have a significant impact on choosing decisions, (5) ) place has no significant impact on choosing decisions, (6) physical evidence has a significant impact on choosing decisions, (7) process has a significant impact on choosing decisions, (8) people have a significant impact on choosing decisions, (9) brand image and marketing mix together- have a significant impact on the decision to choose. Based on this analysis it can be concluded that brand image and marketing mix simultaneously or partially have a significant impact on the decision to choose LPK Royal Bali College.